COPING MECHANISM USED BY DEPENDENT ELDERLY IN REJOWINANGUN URBAN VILLAGE, YOGYAKARTA - Sari, Cynthia Kumala; Widagdo, The Maria Meiwati; Sigilipoe, Mitra Andini (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Introduction: A decrease often follows aging in quality of life. Coping is a form of problem-solving and balancing emotions in stressful situations. Coping strategies that someone uses extensively affect someone's ability to handle problems.Objectives: Obtain an overview of the coping mechanism of dependent elderly in Rejowinangun Urban Village, Yogyakarta, and indirectly know the impact of the COVID-19 pandemic on dependent elderly.Materials and Methods: The subjects were more than 60 years old residents of Rejowinangun Urban Village, which are dependent on Barthel's criteria and had no cognitive impairment. A qualitative method with a phenomenological approach was used. Data collection was carried out by in-depth interviews, which were preceded by a screening process. Sampling was done through purposive sampling with five subjects. The interview was verbatim transcribed and analyzed using the thematic framework.Results: Dependent elderly perform confrontative, seeking social support, planful problem solving, self-control, distancing, positive reappraisal, escape/avoidance, and accepting responsibility coping. Not all dependent elderly living depend on others. Some do not want to bother others and are still productive. More diverse coping mechanisms were carried out by subjects who had the disease for more than ten years.Conclusion: Subjects tend to use problem-focused coping rather than emotion-focused coping. During the COVID-19 pandemic, their disease can become uncontrollable, and they feel stressed because they cannot do outside activities or the decreased income. However, they have more time to spend with their families.